International development assistance in forestry and land management: the process and the players - Byron, R.N. (1997)
“Why do so many forestry aid projects fail?” is a question being asked more frequently. Most replies list technical difficulties in implementation. However, this paper argues that the answer can only be found through understanding two much more general processes; how a forestry activity relates to the broader socio-economic context in which it is embedded; and how development assistance operates in practice. Many projects which professional foresters see as failures in technical or even humanitarian terms may have been successful according to other political or commercial criteria, or to the tests of other interest groups. In spite of the constrains inherent in the international development process, many forestry projects have successfully delivered real and lasting benefits to societies, economies and the environment. Projects, especially ones of social forestry character, will continue to fail if design and implementation do not pay attention to the needs of the target group, the poor.